Cost-effectiveness of internet-delivered cognitive behaviour therapy for body dysmorphic disorder: Results from a randomised controlled trial - Oskar Flygare; Erik Andersson; Gjermund Glimsdal; David Mataix-Cols; Diana Pascal; Christian Rück; Jesper Enander (Internet Interventions, 2023)
Objectives: To evaluate the cost-effectiveness of internet-delivered cognitive behaviour therapy for body dysmorphic disorder (BDD-NET). Design: Secondary cost-effectiveness analysis from a randomised controlled trial on BDD-NET versus online supportive psychotherapy. Setting: Academic medical center. Participants: Self-referred adult participants with a primary diagnosis of body dysmorphic disorder and a score of 20 or higher on the modified Yale-Brown Obsessive Compulsive Scale for BDD (n = 94). Patients receiving concurrent psychotropic drug treatment were included if the dose had been stable for at least two months. Interventions: Participants received either BDD-NET (n = 47) or online supportive psychotherapy (n = 47) for 12 weeks. Primary and secondary outcome measures: The primary outcome measures were cost-effectiveness and cost-utility from a societal perspective, using remission status from a diagnostic interview and quality-adjusted life years (QALY), respectively. Secondary outcome measures were cost-effectiveness and cost-utility from a health care perspective and the clinic's perspective. Results: Compared to supportive psychotherapy, BDD-NET produced one additional remission for an average societal cost of $4132. The cost-utility analysis showed that BDD-NET generated one QALY to an average cost of $14,319 from a societal perspective. Conclusions: BDD-NET is a cost-effective treatment for body dysmorphic disorder, compared to online supportive psychotherapy. The efficacy and cost-effectiveness of BDD-NET should next be directly compared to in-person cognitive behaviour therapy. Trial registration: NCT02010619.